2012
DOI: 10.1093/deafed/ens020
|View full text |Cite
|
Sign up to set email alerts
|

First Information Parents Receive After UNHS Detection of Their Baby's Hearing Loss

Abstract: The first information parents receive after referral through Universal Newborn Hearing Screening (UNHS) has significant consequences for later care-related decisions they take and thus for the future of the child with a hearing loss. In this study, 11 interviews were conducted with a representative sample of Flemish service providers to discover (a) the content of the information provided to parents and (b) the service providers' assumptions and beliefs concerning deafness and care. To do this, we conducted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Caregivers of children with hearing loss are required to make several important decisions about their child’s early intervention not only after the diagnosis of the hearing loss, but throughout their child’s entire early intervention process. These decisions typically center around their child’s use of hearing devices, including hearing aids or cochlear implants (Matthijs et al., 2012), and their child’s method or mode of communication, specifically, the decision to implement oral language, sign language, or a combination of both oral and sign language (Decker, Vallotton, & Johnson, 2012). It is this decision regarding the child’s method of communication which Marschark (2007) describes as one of the most important issues that families of children with hearing loss must address.…”
mentioning
confidence: 99%
“…Caregivers of children with hearing loss are required to make several important decisions about their child’s early intervention not only after the diagnosis of the hearing loss, but throughout their child’s entire early intervention process. These decisions typically center around their child’s use of hearing devices, including hearing aids or cochlear implants (Matthijs et al., 2012), and their child’s method or mode of communication, specifically, the decision to implement oral language, sign language, or a combination of both oral and sign language (Decker, Vallotton, & Johnson, 2012). It is this decision regarding the child’s method of communication which Marschark (2007) describes as one of the most important issues that families of children with hearing loss must address.…”
mentioning
confidence: 99%
“…Throughout the diagnostic process, parents of children with hearing loss typically move through a cycle of grief, including shock, recognition, denial, acknowledgement, and action (Kampfe, 1989; Kurtzer-White & Luterman, 2003). During this emotional time, parents are expected to make significant decisions regarding their child’s early intervention, often very quickly following the diagnosis (Decker, Vallotton, & Johnson, 2012; Matthijs et al, 2012). One of the first decisions that must be made concerns the use of hearing technology, including hearing aids and cochlear implants (Matthijs, et al, 2012).…”
mentioning
confidence: 99%
“…Our studies indicate that starting from screening and throughout attendance of rehabilitation centres and ear-nose-throat (ENT) hospital departments, most hearing parents placed deafness within a medical framework, because they became confronted with professionals trained to operate in issues of deafness from a predominantly medical perspective (Hardonk et al 2011c). This was also found by Matthijs et al (2012) in their discourse analysis of professionals' support after screening. However, Young (1999) has demonstrated that, depending on how early intervention is organised, the influence originating from formal social support can also fit within a social or cultural-linguistic perspective.…”
Section: Social Supportmentioning
confidence: 54%